The Shaolin cowboy who'll stop the reign? - Darrow, Geof 1955-; Piekos, Nate (Dark Horse Books, 2017)
"The Shaolin Cowboy finds that his road to hell is paved not with good intentions but old nemeses hellbent on bloody revenge... AGAIN!!!! He fought an army of the shambling dead, but can he survive a sinister desert town filled with guns, prostitutes, and white supremacists, all run by a crustaceous mafia?"...